The Implicature of Reddit Memes from r/HistoryMemes Sub-Reddit - Nadia Agatha Pramesthi (Research And Innovation In Language Learning (RILL), 2022)
Memes have been a media of entertainment when the internet has been a part of human’s life. Reddit as a source of a community who shares anything from news, information, gossip, to memes, is the core of this research. Fifty memes taken from a subreddit called r/HistoryMemes became the object of the research. The question is, do the memes exclusively enjoyed by the community or do the memes can also be brought outside the community and people still understand the joke?  Using the Implicature theory, the researcher tries to answer the question. The result is that there is a possibility for the people outside the community of r/HistoryMemes subreddit to understand the joke that is delivered by the meme